Development of inbound tourism in Minsk: sociological modeling - Kabiak, Aleh V. (Journal of the Belarusian State University. Sociology, 2019)
The four-component sociological model of inbound tourism development in Minsk is elaborated in the context of the Max Weberʼs theory of social action. The evolution of motivations for the arrival of foreign tourists in the capital of Belarus is presented as follows: 1) pragmatic motivation; 2) emotionally coloured actions; 3) habitual acts; 4) value-based actions. Original texts are created for each component of the model and they can become the basis for advertising products about Minsk as an attractive tourist center. An imitation interview with a Russian resident, that is motivated for subsequent visits to Minsk and further trips to Belarus, was composed.